2019
DOI: 10.1177/1758835919875851
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of hypoxia-inducible factor-1α in advanced cancer survivors: a meta-analysis with trial sequential analysis

Abstract: Background: Expression of hypoxia-inducible factors (HIFs) has been observed, but their prognostic role in advanced cancers remains uncertain. We conducted a meta-analysis to establish the prognostic effect of HIFs and to better guide treatment planning for advanced cancers. Methods: Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated. Trial sequential analysis (TSA) was also performed. The clinical outcomes included overall survival (OS), disease-free survival (DFS), progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…cancer meta-analyses(95,96). The relative risks of high expression of HIF-1, MVD, VEGF, CA9, and other hypoxic markers are only moderate compared to known clinical prognostic factors that already represent the aggressive phenotype associated with HIFs (e.g.…”
mentioning
confidence: 99%
“…cancer meta-analyses(95,96). The relative risks of high expression of HIF-1, MVD, VEGF, CA9, and other hypoxic markers are only moderate compared to known clinical prognostic factors that already represent the aggressive phenotype associated with HIFs (e.g.…”
mentioning
confidence: 99%
“…Moreover, HIF-1α expression has been associated with worse prognosis in advanced cancer patients treated with chemotherapy and/or radiotherapy; thus, in addition to a useful biomarker, targeting HIF-1α could be an interesting therapeutic approach to improve survival in advanced cancer patients. 68 Here, significant results were observed in some clinicopathological features, including BCLC staging, capsule infiltration, intrahepatic metastasis, lymph node metastasis, TNM classification, tumor differentiation, tumor number, tumor size (contrasting greater or less than 3 cm), vascular invasion and vasculogenic mimicry. After subgroup analysis according to sample size and NOS score, we also observed a possible HIF-1α correlation with AFP levels, cirrhosis, tumor size (5 cm) and albumin, while histological grade showed association after removing one study.…”
Section: Discussionmentioning
confidence: 79%
“…Increased HIF1 expression is associated with overall poorer survival in breast cancer patients [ 169 ], and several studies directly or indirectly implicate HIF1-α in the diabetes-breast cancer crosstalk. A study conducted in 2015, reported HIF1 mediated advancement of breast metastasis in comorbid patients [ 170 ], however the article cannot be fully reviewed, as it was excluded based on language discrepancy.…”
Section: Hif1’s Regulation Of the Multilayered Relationship Between T2dm And Breast Cancermentioning
confidence: 99%